Enhancing the Selection Process in Architectural Services - Kim, Sangchul; woon Kim, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives: Construction industry has a lot of influence on human life, so most countries have enacted law on construction and construction business is completed through various stages. Methods/Statistical analysis: The stages contain 5 stages, which are pre-design, design, pre-construction, construction, and post-construction. And they can be divided into design and construction in the largest category. The architectural design field, which was the main field of the construction service industry in the construction industry, was searched by the law focusing on the designer selection method which had the greatest influence on the design stage. Findings: The research team examined what kind of business was going on and tried to analyze what kind of problem is from a realistic point of view. In particular, the research team analyzed the design stage from a legal standpoint, searched Act on Contracts to which the State is a Party, Architecture Act, Framework Act on the Construction Industry, Construction Technology Promotion Act, Building Service Industry Promotion Act, and Certified Architects Act. As a results, problems with the design competition, problems with protection from design, problems of time in complicated processes were abstracted. Also, systems that conflict with the design industryâ€™s market arise, the company is limiting the opportunities for architectural design to advance. Therefore, this thesis presents ways to solve the problem by simplifying the design completion system, ensuring compliance with the design protection device, and complying with the appropriate design period. Improvements/Applications: The research team tried to solve the problems in the field of construction design by simplifying design competition method, design protection device, and adhering to proper design period as an alternative. Â